Drug-specific risk of non-tuberculosis opportunistic infections in patients receiving anti-TNF therapy reported to the 3-year prospective French RATIO registry. Issue 4 (21st December 2010) - Salmon-Ceron, D; Tubach, F; Lortholary, O; Chosidow, O; Bretagne, S; Nicolas, N; Cuillerier, E; Fautrel, B; Michelet, C; Morel, J; Puéchal, X; Wendling, D; et al.
Abstract : Background: Anti-tumour necrosis factor (TNF) therapy may be associated with opportunistic infections (OIs). Objective: To describe the spectrum of non-tuberculosis OIs associated with anti-TNF therapy and identify their risk factors. Methods: A 3-year national French registry (RATIO) collected all cases of OI in patients receiving anti-TNF treatment for any indication in France. A case–control study was performed with three controls treated with anti-TNF agents per case, matched for gender and underlying inflammatory disease. Results: 45 cases were collected of non-TB OIs in 43 patients receiving infliximab (n=29), adalimumab (n=10) or etanercept (n=4) for rheumatoid arthritis (n=26), spondyloarthritides (n=3), inflammatory colitis (n=8), psoriasis (n=1) or other conditions (n=5). One-third (33%) of OIs were bacterial (4 listeriosis, 4 nocardiosis, 4 atypical mycobacteriosis, 3 non-typhoid salmonellosis), 40% were viral (8 severe herpes zoster, 3 varicella, 3 extensive herpes simplex, 4 disseminated cytomegalovirus infections), 22% were fungal (5 pneumocystosis, 3 invasive aspergillosis, 2 cryptococcosis) and 4% were parasitic (2 leishmaniasis). Ten patients (23%) required admission to the intensive care unit, and four patients (9%) died. Risk factors for OIs were treatment with infliximab (OR=17.6 (95% CI 4.3 - 72.9); p<0.0001)or adalimumab (OR=10.0 (2.3 to 44.4); p=0.002) versus etanercept, and oral steroid use >10 mg/day or intravenous boluses during the previous year (OR=6.3 (2.0 to 20.0); p=0.002). Conclusion: Various and severe OIs, especially those with intracellular micro-organisms, may develop in patients receiving anti-TNF treatment. Monoclonal anti-TNF antibody rather than soluble TNF receptor therapy and steroid use >10 mg/day are independently associated with OI.